Prevalence and associated risk factors among patients with overactive bladder syndrome in Pakistan - Rashid, Sajid (Pak J Med Sci, 2021)
OBJECTIVES: To determine the Prevalence and associated risk factors among patients with overactive bladder syndrome in Pakistan. METHODS: This was a community-based, face to face, cross sectional survey to calculate the prevalence and its associated risk factors. A sample of 1058 patients, women and men aged between 35 to 60 years having symptoms of overactive bladder was selected through convenience sampling from different cities of Pakistan during September to December 2020. Data was collected by using an Overactive Bladder Scoring System (OABSS) tool for prevalence and a developed questionnaire to rule out the risk factors. RESULTS: The prevalence was 27.4% (n=289) and it increased with age. The average ages for women and men were 44.60±7.88 and 46.14±7.69 years respectively. The OAB prevalence was the lowest among the participants aged 35-43 years 15.2% (n=55) while it was highest among those who were aged 53-60 years 49.6%, (n=127). The age, body mass index, diabetes mellitus, income, family history, parity and urinary tract infection were found to be significant associated risk factors for overactive bladder with p value <0.05. CONCLUSION: The overall prevalence of overactive bladder was 27.4% and it does not differ by gender, hypertension, pelvic surgery, smoking, constipation and sleep while it has significant association with age, body mass index, diabetes mellitus, income, parity and urinary tract infections.